Relationship Between Consumer Behavior Factors Towards Purchase Intention Case Study: Urban Farming Products (Journal of Innovation, Business and Entrepreneurship, 2020)
Urban farming industry is still at early stage in Indonesia. But the growth of the industry is increasing time by time since Indonesia people started to aware about surrounding environment moreover their own health. Urban farming, producing organic food products without using land as its platform, replaced by water-based planting, and can be placed flexibly in most of places. Because of the rapid growth of the industry it is important to know consumer perspective toward urban farming products. Therefore, this research aims to find out the relationship between consumer perspectives and purchase intention on urban farming products. Data is collected by distributing online questionnaire and analyzed using multivariate regression. In this research, the independent variable is consumer behavior that divided into factors which are consumer awareness, perception, and motivation while the dependent variable is purchase intention. The result is the independent variables are influencing the dependent variable simultaneously and partially. While the most influencing factor is motivation towards purchase intention regarding urban farming products.Keywords: Urban Farming, Consumer Behavior, Consumer Awareness, Perception, Motivation, Purchase Intention, Indonesia.